Non-thermal atmospheric pressure plasma-irradiated cysteine protects cardiac ischemia/reperfusion injury by preserving supersulfides - Akiyuki Nishimura; Tomohiro Tanaka; Kakeru Shimoda; Tomoaki Ida; Shota Sasaki; Keitaro Umezawa; Hiromi Imamura; Yasuteru Urano; Fumito Ichinose; Toshiro Kaneko; Takaaki Akaike; Motohiro Nishida (Redox Biology)
Ischemic heart disease is the main global cause of death in the world. Abnormal sulfide catabolism, especially hydrogen sulfide accumulation, impedes mitochondrial respiration and worsens the prognosis after ischemic insults, but the substantial therapeutic strategy has not been established. Non-thermal atmospheric pressure plasma irradiation therapy is attracted attention as it exerts beneficial effects by producing various reactive molecular species. Growing evidence has suggested that supersulfides, formed by catenation of sulfur atoms, contribute to various biological processes involving electron transfer in cells. Here, we report that non-thermal plasma-irradiated cysteine (Cys∗) protects mouse hearts against ischemia/reperfusion (I/R) injury by preventing supersulfide catabolism. Cys∗ has a weak but long-lasting supersulfide activity, and the treatment of rat cardiomyocytes with Cys∗ prevents mitochondrial dysfunction after hypoxic stress. Cys∗ increases sulfide-quinone oxidoreductase (SQOR), and silencing SQOR abolishes Cys∗-induced supersulfide formation and cytoprotection. Local administration of mouse hearts with Cys∗ significantly reduces infarct size with preserving supersulfide levels after I/R. These results suggest that maintaining supersulfide formation through SQOR underlies cardioprotection by Cys∗ against I/R injury.